Investigation of calcium carbonate precipitation in the presence of carboxymethyl inulin - Kirboga, Semra; Oner, Mualla (ROYAL SOC CHEMISTRY, 2013)
The aim of this work is to study the effect of a water-soluble biopolymer, carboxymethyl inulin (CMI), on the crystallization of calcium carbonate. We have investigated the effect of the feed rate of the reactant and the concentration of the biopolymer on the surface area, particle size and size distribution, final morphology and polymorph of calcium carbonate crystals during a precipitation. The produced crystals were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectrometry (FT-IR), X-ray diffraction (XRD), thermal analysis (TGA-DTA) and BET (Brunauer-Emmett-Teller) methods. In the presence of the biopolymer (0.5-1 g L-1), the polymorph of the synthesized calcium carbonate crystals changed from pure calcite to a mixture of vaterite and calcite. The formation of a thermodynamically unstable vaterite phase was attained in the presence of the biopolymer.
Keywords: CRYSTAL-GROWTH; SEEDED GROWTH; ABALONE SHELL; CRYSTALLIZATION; CACO3; TRANSFORMATION; PARTICLES; SILICA; BIOMINERALIZATION; POLYELECTROLYTES; Chemistry; Crystallography